Perempuan Dan Stigma Hukum Dalam Kasus Pelecehan Seksual: Reviktimisasi Dan Ketimpangan Gender Di Indonesia - Chantika Dwi Oktaviani; Nazila Lestari; Handra Anie (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
Sexual harassment cases in Indonesia not only cause physical and psychological harm to victims but also reveal persistent gender inequalities within the country’s legal system and social culture. This study aims to explore how social stigma and gender bias influence the treatment of female victims of sexual harassment and contribute to revictimization—situations where victims are blamed or further harmed during legal processes. Using a qualitative socio-legal approach, the research analyzes legal documents, case studies, and interviews with victims, legal advocates, and law enforcement officers. The findings indicate that legal proceedings often reinforce stigma against victims through moral judgments and questions that implicitly blame women. Revictimization arises from the dominance of patriarchal values that shape legal actors’ perceptions of victims’ credibility. This study highlights the urgent need for gender-sensitive legal reforms, greater empathy and awareness among law enforcement officers, and a broader social paradigm shift to ensure that female victims of sexual harassment receive fair and nondiscriminatory access to justice.